2004
DOI: 10.1074/jbc.m408113200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of IQGAP1 Modulates Its Binding to Cdc42, Revealing a New Type of Rho-GTPase Regulator

Abstract: The Rho-GTPase Cdc42 is important for the establishment and maintenance of epithelial polarity. Signaling from Cdc42 is propagated via its effector molecules that specifically bind to Cdc42 in the GTP-bound form. The cell-cell contact regulator and actin-binding protein IQGAP1 is described as effector of Cdc42 and Rac. Unexpectedly, we show in this study that IQGAP1 bound also directly nucleotide-depleted Cdc42 (Cdc42-ND). This interaction was enhanced in the presence of phosphatase inhibitors and in epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
92
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 42 publications
11
92
0
Order By: Relevance
“…All cells had equal levels of endogenous total CDC42, as demonstrated in the lower panel in Fig. 9, and these results are not unique to ␤-cells, because they confirm similar findings from other cell types (Fukata et al, 2002;Mataraza et al, 2002;Grohmanova et al, 2004), affirming an apparently conserved function for IQGAP1 upstream of CDC42 (Osman et al, 2002). These data help explain why IQGAP1-C disrupts binding, secretion and protein synthesis, confirming that active CDC42 negatively regulates IQGAP1 function in secretion.…”
Section: Interplay Between Cdc42 and Iqgap1 Regulates Secretionsupporting
confidence: 73%
See 2 more Smart Citations
“…All cells had equal levels of endogenous total CDC42, as demonstrated in the lower panel in Fig. 9, and these results are not unique to ␤-cells, because they confirm similar findings from other cell types (Fukata et al, 2002;Mataraza et al, 2002;Grohmanova et al, 2004), affirming an apparently conserved function for IQGAP1 upstream of CDC42 (Osman et al, 2002). These data help explain why IQGAP1-C disrupts binding, secretion and protein synthesis, confirming that active CDC42 negatively regulates IQGAP1 function in secretion.…”
Section: Interplay Between Cdc42 and Iqgap1 Regulates Secretionsupporting
confidence: 73%
“…9A). IQGAP1 also binds nucleotidedepleted CDC42 (ND-CDC42) and GDP-CDC42 (Grohmanova et al, 2004), confirming its GEF-like activity on CDC42 and providing an explanation as to why wild-type CDC42 blocked both interaction and secretion (Figs 1 and 8) similar to its dominant active mutants, indicating that increasing the level of CDC42 enhances the pool of its active form, leading to the observed inhibition.…”
Section: Interplay Between Cdc42 and Iqgap1 Regulates The Function(s)mentioning
confidence: 67%
See 1 more Smart Citation
“…We and others have previously shown that IQGAP1 is phosphorylated in cells in a PKC⑀-dependent manner at Ser 1443 in response to phorbol ester treatment (28,37). It seems reasonable, therefore, to hypothesize that IQGAP1 can be phosphorylated on Ser 1443 in response to EGF-stimulated activation of EGFR.…”
Section: Iqgap1 and Egfr Interact In Cells-iqgap1mentioning
confidence: 99%
“…EGFR triggers phospholipase C␥ to generate both diacylglycerol and inositol 1,4,5-trisphosphate-mediated calcium fluxes, resulting in the potential activation of multiple PKC isoforms (40,41). Previous studies have shown that Ser 1443 is contained within a PKC⑀ consensus site and that PKC⑀ is able to catalyze IQGAP1 phosphorylation at this site in vitro (28,37). To further characterize PKC involvement in EGF-mediated phosphorylation of IQGAP1, we performed targeted knockdown of the TPA-responsive PKC isoenzymes expressed in HeLa cells (42).…”
Section: Iqgap1 and Egfr Interact In Cells-iqgap1mentioning
confidence: 99%